Understanding religious worldviews: concepts and roles through inter-religious dialogue in shaping a better future for humanity - Ali, Md. Yousuf; Osmani, Noor Mohammad (2011)
Every religion has its own worldview that provides an outlook of life for perceiving the reality and truth with a sense of its meaning and values. The essence of religious faith shapes people’s attitudes, perceptions, conducts, actions, and enhances the relationships between man-God-universe. In this process, people who adhere to a particular religion tend to explore the phenomena through the lens of religion. However, throughout the history of religion, it has been observed that religious worldviews provoked people to live with peace, love, and co-existence on the one hand, with conflict, violence, and destruction on the other (i.e., Crusades of Christian Europe against Muslims, and Islamophobia). In contemporary time, after the post-9/11, the world community observes hatred, violence, conflict, and aggression between the Muslims and non-Muslims because of propagation against Islam and Muslims, prejudice and unequivocal ignorance. In these turmoil situations, inter-faith dialogue is a vital requirement for establishing world peace and security, and for reducing hatred and conflict that will strengthen to shape a better prosperous future for the entire humanity. Therefore, this article aims to understand the concept of religious worldview and its role in shaping a better prosperous and affluent future for humanity. Particularly this study focuses on: a) understanding the concepts and roles of religious worldviews, b) illustrating how to utilize comprehensively the inter-religious dialogue as a method in enhancing the bridge among people of different faiths for a prosperous future for entire humanity, c) elaborating vibrant methodologies and principles for fruitful religious dialogue among major world religions that explore the common grounds and common values towards understanding each other in this globalized era, d) providing pragmatic recommendations on devising versatile strategies for prolific dialogue among religions in order to make the world a better place to live in with peace, justice and co-existence. Discussion would include implications of the research findings, shortcomings of the current study, and directions for future research.